PEMANFAATAN TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN KOSA KATA BAHASA INGGRIS - Riski Sulistiyaningsih; Deni Syamsu Rakhmanto; Ichwan Kurniawan; Nur Fadhilah (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2021)
The purpose of this study is to determine the use of augmented reality technology as a medium for learning English vocabulary. The research method used is the method of developing learning media which refers to Luther's multimedia development method. The development stage starts from concept, design, collecting material, assembly, testing, and distribution. All stages in the development method have been carried out and have realized English vocabulary learning media. The subjects of the study were students who had taken English courses at STMIK Widya Pratama. Data collection and testing techniques used interviews and questionnaires. This study uses quantitative descriptive analysis techniques.The results showed that the medium of learning English vocabulary by utilizing augmented reality technology. through testing the Graphical User Interface (GUI) that the application is easy to use and can help learning English vocabulary through the features contained in the application. Meanwhile, through the User Acceptance Test (UAT) that has been carried out, the audiovisual in the application can help explain English vocabulary material. In addition, the application can be used to help learn English vocabulary, both in the classroom and outside the classroom.